Fixed Point Theorems for Multivalued Gerghaty Type Contractions via Generalized Simulation Functions: Azhar Hussain, Ahsan Ali, Nuttapol Pakkaranang, Nopparat Wairojjana - Team, Support (Thai Journal of Mathematics, 2020)
The aim of this paper is to introduce the notion of a multivalued Gerghaty type contractive mapping via simulation functions along with C-class functions and prove some fixed point results. As consequences, we derive some fixed point results endowed with graph. An example is given to show the validity of our results given herein.